Pengembangan Media Pmbelajaran Interaktif Berbasis Augmented Reality pada Sistem Instalasi Tata Udara: Development of Augmented Reality-Based Interactive Learning Media in Air Conditioning Installation Systems - Gede Arya Palguna; I Gede Wiratmaja; Edy Agus Juny Artha (Jurnal Pendidikan Teknik Mesin Undiksha, 2026)
The lack of Augmented Reality (AR) learning media for the air conditioning installation system course at SMK Negeri 3 Singaraja has made it difficult for students to understand how the system works. This study aims to develop Augmented Reality (AR)-based learning media using the ADDIE development model to analyze the feasibility of the prototype from the perspectives of learning media experts and subject matter experts. Data collection methods used questionnaires, and the data was analyzed using percentage calculations. The results of the data analysis indicate that this learning medium is highly feasible based on the assessment by subject matter experts with a percentage of 94.28%, as well as from the product feasibility test conducted by learning media experts, yielding a product feasibility percentage of 85.71%. Based on these results, this learning media can be implemented as a supplement in the classroom learning process.